Dynamical effects on superradiant THz emission from an undulator. (11th April 2019) - Geloni, Gianluca; Tanikawa, Takanori; Tomin, Sergey
Abstract : The large dispersion in undulators tuned at resonance in the THz range can be responsible for a change in the electron beam form factor in the case of the presence of energy chirp, leading to enhancement or suppression of superradiant THz emission. Abstract : Superradiant emission occurs when ultra‐relativistic electron bunches are compressed to a duration shorter than the wavelength of the light emitted by them. In this case the different electron contributions to the emitted field sum up in phase and the output intensity scales as the square of the number of electrons in the bunch. In this work the particular case of superradiant emission from an undulator in the THz frequency range is considered. An electron bunch at the entrance of a THz undulator setup has typically an energy chirp because of the necessity to compress it in magnetic chicanes. Then, the chirped electron bunch evolves passing through a highly dispersive THz undulator with a large magnetic field amplitude, and the shape of its longitudinal phase space changes. Here the impact of this evolution on the emission of superradiant THz radiation is studied, both by means of an analytical model and by simulations.